P578 Exploring duration of corticosteroid withdrawal in definitions of corticosteroid-free remission endpoints in ustekinumab clinical trials: results from the IM-UNITI, UNIFI, and SEAVUE trials. (30th January 2023) - Panés, J; Panaccione, R; Sands, B; Gasink, C; Marano, C; Ma, T; Hoops, T
Abstract: Background: Remission off steroids is a major treatment goal in inflammatory bowel disease. In the recent CORE-IBD consensus, 1 the preferred definition of "corticosteroid-free" remission in clinical trials was withdrawal ≥12 weeks before the assessment timepoint. We evaluated the rates of corticosteroid-free remission according to three different definitions (ie, cross-sectional, ≥30, and ≥90 days) in the analysis of the corticosteroid-free remission endpoint using data from the IM-UNITI and SEAVUE trials of patients with Crohn's disease (CD) and the UNIFI trial of patients with ulcerative colitis (UC). Methods: In IM-UNITI and UNIFI, patients with moderate-to-severe CD and UC, respectively, who had previously responded to ustekinumab (UST) induction were randomized to placebo (PBO), UST 90mg SC q12w, or UST 90mg SC q8w. In SEAVUE, biologic naïve patients with moderate-to-severe CD were randomized to adalimumab 160mg SC at week 0, 80mg SC at week 2, and 40mg SC q2w or UST ~6mg/kg IV at week 0 and 90mg SC q8w. Each trial included protocols for mandatory corticosteroid tapering after the induction phase unless medically inappropriate (required in IM-UNITI and UNIFI starting at week 8 and recommended in SEAVUE starting at week 8 but required starting at week 16). Corticosteroid-free remission was defined as clinical remission (CDAI<150 in IM-UNITI and SEAVUE and a Mayo score ≤2 with no individual subscore >1 in UNIFI) and not receiving steroids at the assessment timepoint or ≥30 or ≥90 days before the assessment timepoint. Corticosteroid-free remission at week 44 was a major secondary endpoint in IM-UNITI and UNIFI (both cross-sectional). Corticosteroid-free remission (≥30 days before week 52) was a major secondary endpoint in SEAVUE. Results: The proportions of patients who achieved corticosteroid-free remission were consistent, regardless of the corticosteroid-free duration used in the assessment (Tables 1 and 2). The results were consistent for both ustekinumab treatment groups (q12w and q8w) and placebo in the pivotal IM-UNITI and UNIFI studies (Table 1) and for both ustekinumab and adalimumab groups in the SEAVUE study (Table 2). Conclusion: In CD and UC clinical trials of ustekinumab maintenance, which included protocol-mandated corticosteroid tapering regimens, corticosteroid-free remission results at 1 year were similar regardless of the corticosteroid-free duration used in the outcome definition. References: 1) Ma C, Hanzel J, Panaccione R, et al. CORE-IBD: A Multidisciplinary International Consensus Initiative to Develop a Core Outcome Set for Randomized Controlled Trials in Inflammatory Bowel Disease. Gastroenterol 2022;4:950-64.